MATHEMATICAL MODELING OF INTERSECTIONS OF DIFFERENTLY VERGENT FOLD STRUCTURES - Plotnikov L.M.; Makedon I.D.; Vasil'yev V.M. (My University, 1989)
The authors used computer graphics to develop models of geologic sections in areas of intersection between fold structures of different age when traces of the intersection of the axial planes of sequentially formed structures are parallel to the originally plane-parallel layering of a deformed geologic body. As applied to originally horizontal layering, this case corresponds to an intersection of fold structures with identical strike but different vergence. Development of programs for mathematical modeling the shear deformation of unevenly layered bodies is possible in principle. It is first necessary to devise a mathematical theory reflecting satisfactorily the complex physical patterns associated with such structures.